(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Current Chilean public education policies have established educational inclusion and a new, quality public education system that provides the best opportunities for all its inhabitants, especially the most socially, culturally, and economically vulnerable, as key pillars. In this way, the international commitment mandated by the United Nations in the 2030 Agenda for Sustainable Development, specifically Sustainable Development Goal 4, which seeks to guarantee inclusive and equitable quality education and promote lifelong learning opportunities for all, is fully embraced. This research aims to investigate the attitudes of student teachers toward promoting the development of inclusive schools. It is therefore necessary to understand the thoughts and feelings of one of the main stakeholders who will lead these changes, future teachers. The study was developed using a quantitative, multivariate, descriptive, and correlational model of the phenomenon based on the sample’s general perceptions based on the construct studied. Data collection was carried out by adapting the "Questionnaire for Future Secondary Education Teachers on Perceptions of Attention to Diversity" (Colmenero and Pegalajar , 2015) to Chilean reality. The results show a positive perception of inclusion among students, but this needs to be translated into improved initial teacher training and actual inclusion practices.